Solitary nodule thyroid: diagnosis and management - Deepthi, M.; Sukthankar, P. S.; Narsimloo, K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Solitary nodule can be a true solitary nodule or a dominant nodule of multinodular goitre or ectopic thyroid or unilateral agenesis. Solitary nodule can be benign or malignant. Purpose of evaluation is to differentiate between the two. Methods: A prospective study of solitary nodule thyroid (STN) patients presenting to ENT outpatient department, for a period of 3 years from September 2012 to 2015. Results: Out of 67 patients enrolled into study, 53 patients had benign true STN, 9 patients had multinodular goiter (MNG) presenting as solitary nodule and 5 had malignant nodule (7.46%). Among the benign nodules, 25 patients had small solitary nodule (<4 cm size). They were treated medically and followed-up for a period of 1 year. 28 patients with large benign solitary nodules (>4 cm size) were taken up for surgery directly. Hemithyroidectomy was done in benign STN patients (39 patients) and total thyroidectomy was done in malignant nodule and MNG patients and followed-up by lifelong L-T4 therapy. Conclusions: Small benign solitary nodules regress with medical therapy alone. In large solitary nodules, and in those nodules not regressing with medical therapy, hemithyroidectomy is adequate. In MNG and malignant nodules, total thyroidectomy is advocated. Hemithyroidectomy and total thyroidectomy patients were followed - up with suppression and supplementation therapy respectively.This area being fluorotic belt, there is an increased prevalence of goiter. This study gives a concise guideline in evaluation and management of STN for goiter endemic areas.